Information system support for medical secretaries' work in patient administration tasks in different phases of the care process - Jenni Santavirta; Anne Kuusisto; Kaija Saranto; Tarja Suominen; Paula Asikainen (Finnish Social and Health Informatics Association, 2021)
Medical secretaries may have several separate electronic nursing information systems in use, but regardless of the systems, their task is to make sure that the patient information is correct and usable. The purpose of this study is to describe the support provided by the hospital information systems for the work of medical secretaries in patient administration tasks in different phases of the care process. The data were collected in a central hospital where medical secretaries had long been using partly electronic information systems. The data were collected using an abridged version of the Hospital Information System Monitor (HIS-monitor). The majority of the secretaries (N=60) gave a positive assessment for the support provided by the information system for their work at patient admission, when ordering diagnostic or therapeutic examinations or procedures, and at patient discharge. In the planning and organization of care, most thought that the systems provided poor support for informing all those involved in patient care. At patient admission, nearly half considered that the support for ensuring data protection (46%) and the systems' compliance with legal obligations (44%) was poor. In connection with ordering diagnostic and therapeutic examinations and procedures, nearly half (43%) thought that information on the availability in ancillary units was not readily and easily available. At patient discharge, 40% considered that the systems did not support the identification of missing or incorrect information. The hospital information system provides partial support for medical secretaries' work. The implementation of fully electronic systems and their functions may improve the support.